Load Transfer On Bored Pile Foundation Instrumented With Fiber Optic And Concrete Quality Analysis - Kevin Martandi Setianto; Cecilia Lauw Giok Swan; Paulus Pramono Rahardjo (U Karst, 2021)
The problem in the construction method of the bored pile is the contamination of mud or the other contaminant that can cause the modulus of elasticity of concrete to decrease. This research determines the modulus of concrete on a bored pile foundation instrumented with fiber-optic (FO) with a manual calculation based on strain data during loading test, validated with the results of research in the laboratory and numerical analysis. Fiber optic was used to measure the strain along with the pile during the loading test. The bored pile foundation is divided into 12 segments with the same strain characteristics, and then the modulus value is calculated. The result is the modulus value of each segment is different, and the value of the modulus changes along with the increase in strain; the modulus will decrease as the strain increases. This differs from the theory that the modulus has a fixed value approximated by empirical equations. Made a cylindrical concrete sample on both sides, which installed a FO to record the strain during the loading test. The result is true that the modulus is not constant but decreases as the strain increases. It is shown in the result of analysis to fiber-optic measurement data. Created a model in Plaxis2D for validation, and the results are not much different from the manual calculation.